Proposal of resistance exercise for people with multiple sclerosis: a case study - Furtado, Otávio Luis Piva da Cunha; Tavares, Maria da Consolação Gomes Cunha Fernandes (Acta Fisiátrica, 2007)
In this study we sought to standardize, propose and apply an adapted resistance exercise program for a group of people with multiple sclerosis (MS). An invitation was made to 80 people attending an institution for people with MS in the city of Campinas, state of Sao Paulo, Brazil. Neurological disability and impairment were determined by the Expanded Disability Status Scale (EDSS). To evaluate the functional capacity we used the Functional Independence Measure (FIM), walking time (10 feet), the Timed “Up and Go” test, the Box and Block test and the Functional Reach test. The resistance exercise program lasted 10 weeks with two weekly sessions. The nine participants were divided in Group 1 (4 sedentary people) and Group 2 (5 people that regularly participated in other physical exercise programs). One individual from Group 1 completed the program with high compliance, showing no alterations at the EDSS and FIM scores. There was a reduction in the 10 feet walking time (- 21%) and at the Timed “Up and Go” test time (- 12.8%). The Box and Block test showed improvement: dominant limb (2.1%) and non-dominant limb (6.7%), but the Functional reach test deteriorated (- 7.5%). The results of this study are in agreement with the international literature, indicating the adequacy and safety of a resistance exercise program in the improvement of functional aspects for people with MS.